Unsaturated fatty acid as functional food for the treatment of Diabetes mellitus type 2 (Research, Society and Development, 2021)
Several studies have been demonstrating to a relationship between unsaturated fatty acids, improvement of pancreatic function and insulin secretion. In this context, this review presents the most recent findings on the pathophysiology of type 2 diabetes mellitus, the action mechanism of unsaturated fatty acids on pancreatic function, and clinical studies in diabetic patients. We evaluated here articles from MedLine/PubMed and the Science direct database, published between 2014 and 2020. Of the 637 results, 13 were selected. From their analysis, we could observe that mono and polyunsaturated fatty acids can improve glycemic control as well as reduce cardiovascular risk. The most recurrent antidiabetic action regarding monounsaturated fatty acids is the ability to preserve insulin signaling, whereas polyunsaturated fatty acids action consists in the increasing expression of the type 4 glucose transporter. However, a complete understanding of the relationship between fatty acids, insulin and inflammation should be considered in future investigations.